Korelasi Kinerja Pegawai Terhadap Keberhasilan Pendaftaran Tanah Sistematik Lengkap (PTSL) Tahun 2017 (Studi Kasus di Kantor Pertanahan Kabupaten Semarang) - Waode Rima Pratiwi; Suharno Suharno; Dwi Wulan Titik Andari (Tunas Agraria, 2019)
Abstract: The Implementation of Complete Systematic Land Registration (PTSL) 2017 at the Land Office of Semarang Regency successfully completed the entire target of 50,000 fields with achievement of 100% realization. The success of a Complete Systematic Land Registration (PTSL) activity is related from the Executor (ASN) side of the activity which will relate to the performance of the employees in carrying out PTSL activities, so it is necessary to prove this in order to optimize the performance of employees and various factors that support the performance of these employees in carrying out activities in accordance with the planned targets. This research is a survey research quantitative approach with research location in Land Office of Semarang Regency. Technique of data collection used are spreading questionnaires to respondents and study documents. Technique of data analysis is conducted by using Pearson Product Moment (PPM) correlation analysis using Statistical Product and Service Solutions (SPSS) program. The results showed that based on the test results of each employee performance supporting variable the most dominant positive and significant correlations were member variables, as evidenced by the correlation coefficient value r = 0.393 *, p-value = 0.029 with a significance of 97.1%, if the ability of members improved it will increase success in implementing PTSL. Overall, a significant positive correlation between employee performance against the success of PTSL implementation in 2017, as evidenced by the correlation coefficient r = 0.360, p-value = 0.016 with a significance of 98.4%, if the factors that affect employee performance are improved it will increase success in PTSL implementation. Based on the test results, the research hypothesis can be accepted. Keywords: correlation, employee performance, PTSL. Intisari: Pelaksanaan Pendaftaran Tanah Sistematik Lengkap (PTSL) Tahun 2017 di Kantor Pertanahan Kabupaten Semarang berhasil menyelesaikan seluruh target 100 %. Keberhasilan PTSL berhubungan erat dengan Pelaksana (ASN), penelitian ini dilakukan untuk mengetahui faktor yang mendukung kinerja pegawai dalam melaksanakan kegiatan PTSL. Metode penelitian dilakukan secara kuantitatif, analisa data dilaksanakan menggunakan analisis korelasi Pearson Product Moment (PPM). Hasil penelitian menunjukkan bahwa masing-masing variabel pendukung kinerja pegawai yang paling dominan berkorelasi positif dan signifikan adalah variabel anggota, terbukti dengan nilai koefisien korelasi korelasi r=0.393*, p-value= 0.029 dengan signifikasi sebesar 97.1%, jika kemampuan anggota ditingkatkan maka akan meningkatkan keberhasilan dalam pelaksanaan PTSL. Secara keseluruhan, korelasi positif yang siginifikan antara kinerja pegawai terhadap keberhasilan pelaksanaan PTSL Tahun 2017, terbukti dengan nilai koefisien korelasi r = 0.360, p-value= 0.016 dengan signifikasi sebesar 98.4%, jika faktor-faktor yang mempengaruhi kinerja pegawai ditingkatkan maka akan meningkatkan keberhasilan dalam pelaksanaan PTSL. Kata kunci: korelasi, kinerja pegawai, PTSL.